Penerapan Program Celengan Kayu dalam Upaya Meningkatkan Karakter Hemat pada Anak Raudatul Athfal - Ainur Risalah; Alisa Alistiana; Ratna Pangastuti; Taseman Taseman; Safarudin Safarudin (JECED : Journal of Early Childhood Education and Development, 2023)
This study aims to describe: (1) implementation of the children's wooden piggy bank program, (2) Obstacles faced and, (3) Suggested solutions This research is qualitative in nature with strategic case studies. The research location is Raudhatul Athfal (RA) Al Ghozali Porong Sidoarjo. Research subjects; Children, Principals, Teachers, and Parents. Collecting research data by means of; observations, interviews, documents, and audiovisual materials. After the data has been collected, data analysis is carried out by means of data condensation, data display, and conclusions drawing. The results of the study: (1) The application of the wooden piggy bank program is carried out every 15 (fifteen) first minutes of class entry or during recess. The wooden piggy bank program is a program to strengthen the character of independence, especially the character of frugal living (2) Constraints faced; there are economic limitations so that no one brings money, lack of awareness and knowledge of parents to routinely carry money that will run out (4) Solutions; teachers need support and patience to create a pleasant saving atmosphere, parents need support to regularly bring money to save according to ability